Enterohemorrhagic Escherichia coli O157:H7: case report - Erdoğan, Haluk; Erdoğan, Aşkın; Levent, Belkıs; Kayali, Revasiye; Arslan, Hande (The Turkish Journal of Pediatrics, 2008)
Enterohemorrhagic Escherichia coli (EHEC) is a significant bacterial pathogen of bloody diarrhea. Not only does it cause systemic complications, such as hemolytic uremic syndrome (HUS) (the most common cause of potentially preventable pediatric renal failure), but it also leads to large outbreaks of bloody diarrhea. Among EHEC serotypes that cause HUS, E. coli O157:H7 is the most common. Herein, we present the case of a young girl with E. coli O157:H7 infection and review the related literature.